GAMBARAN KEJADIAN OBESITAS PADA ANAK SEKOLAH DASAR - Moh Jefriyanto Abas; Misrawatie Goi; Yade Kurnia Yasin (JOURNAL HEALTH AND NUTRITIONS, 2020)
ABSTRACTNutritional status is a condition caused by a balance between the intake of nutrients from food and the nutritional needs of the body. This study aims to describe the nutritional status of children at the State Elementary School 13 Telaga Biru, Gorontalo Regency. This research method is a descriptive survey research, by measuring weight and height to see the nutritional status of students in grades III, IV, V totaling 109 people by taking data at one time. Research Results, Nutritional Status According to BW/U, namely undernutrition (9.7%), good nutrition (74.1%) and overnutrition (16.2%). Nutritional Status According to TB/U, which shows that the prevalence of SDN 13 Telaga Biru Gorontalo Regency students who experience stunting is quite high, namely (26.6%), with a short prevalence (22.9%) and very short (3.7%). Nutritional Status According to BMI/U, the nutritional status is very thin (2.7%), normal (74.4%), fat (9.2%), and Obesity (13.7%). The conclusion is that most students at SDN 13 Telaga Biru, Gorontalo Regency have good nutritional status according to BB/U, some students have stunting nutritional status according to TB/U and some students have normal nutritional status according to BMI/U. ABSTRAKStatus gizi (nutritional status) adalah keadaan yang diakibatkan oleh keseimbangan antara asupan zat gizi dari makanan dan kebutuhan zat gizi oleh tubuh. Penelitian ini bertujuan untuk mengetahui gambaran status gizi anak Sekolah Dasar Negeri 13 Telaga Biru Kabupaten Gorontalo. Metode penelitian ini adalah penelitian survei deskriptif, dengan mengukur berat badan dan tinggi badan untuk melihat status gizi siswa kelas III,IV,V yang berjumlah 109 orang dengan mengambil data dalam satu waktu.Hasil Penelitian, Status Gizi Menurut BB/U yaitu gizi kurang (9,7%), gizi baik (74,1%) dan gizi lebih (16,2%). Status Gizi Menurut TB/U yaitu menunjukan bahwa cukup tinggi prevalensi siswa SDN 13 Telaga Biru Kabupaten Gorontalo yang mengalami Stunting yaitu (26,6%), dengan prevalensi pendek (22,9%) dan sangat pendek (3,7%). Status Gizi Menurut IMT/U yaitu status gizi sangat kurus (2,7%), normal (74,4%), gemuk (9,2%), dan Obesitas (13,7%). simpulan sebagian besar siswa SDN 13 Telaga Biru Kabupaten Gorontalo memiliki status gizi baik menurut BB/U,  sebagian siswa status gizinya Stunting menurut TB/U dan sebagian siswa status gizinya normal menurut IMT/U.